ANALISIS PERHITUNGAN PAJAK PENGHASILAN PASAL 21 PASCA PENERAPAN TARIF PAJAK EFEKTIF RATA-RATA (TER) DIAKHIR TAHUN BAGI WAJIB PAJAK ORANG PRIBADI KARYAWAN TETAP PADA PT. ANUGRAH SEKAYU - Aryani, Farida; Romanda, Candra (Jurnal Ilmiah Akuntansi Rahmaniyah, 2024)
This descriptive study analyzes PPh 21 calculation at the end of the year after TER implementation for WPOP permanent employees at PT. Anugrah. The analysis technique reduces PPh 21 calculation based on Pasal 17 rate with TER. The secondary data analyzed is PPh 21 calculation for 32 WPOP permanent employees. The research results show PPh 21 of 32 permanent employees at the end of the year is based on Pasal 17 rate of Rp. 50,909,825. The payable PPh 21 which has been deducted is IDR. 42,771,769, so there is a difference in taxes still to be paid in 2024 of Rp. 8,138,055. The application of TER is more profitable for low income taxpayers and large family status, while Pasal 17 rate tends to provide higher tax burden, especially for high incomes taxpayers and small family status. Government is expected to apply TER for a year's tax period, that it doesn't make difficult for tax payers by having to recalculate taxes at the end of the year. This creates inefficiencies in tax calculations. PPh 21 calculation payable with a TER is lower than Pasal 17 rate by reducing WPOP's tax burden.